2004
DOI: 10.1002/humu.20050
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of the angiotensin II receptor genesAGTR1 andAGTR2 in women with normotensive pregnancy and women with preeclampsia

Abstract: Angiotensin II (AII) acts as a growth factor in local systems, mediating diverse effects such as cellular proliferation and apoptosis. These effects are controlled through two main receptor subtypes: AGTR1 and AGTR2. We studied the haplotype frequencies of both receptor genes in women with preeclamptic pregnancies and normotensive pregnant women. We also looked for any association between AGTR1 genotype at sites in the 5' flanking region and binding of AII to platelets, which express AGTR1, in 58 normotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
5
34
1
1
Order By: Relevance
“…Decidua is a significant source of extra-renal Ang II production, and the co-expression of both AGTR1 and AGTR2 by decidual stromal cells suggests auto-and paracrine actions in regulating decidual and placental development and function , Herse et al 2007). Genetic studies have suggested a role for AGTR1 in FGR and pre-eclampsia (Plummer et al 2004, Tower et al 2006. It is tempting to speculate that its transient upregulation in cell columns is a requirement for successful trophoblast invasion, and that its failure may play a role in the pathogenesis of pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decidua is a significant source of extra-renal Ang II production, and the co-expression of both AGTR1 and AGTR2 by decidual stromal cells suggests auto-and paracrine actions in regulating decidual and placental development and function , Herse et al 2007). Genetic studies have suggested a role for AGTR1 in FGR and pre-eclampsia (Plummer et al 2004, Tower et al 2006. It is tempting to speculate that its transient upregulation in cell columns is a requirement for successful trophoblast invasion, and that its failure may play a role in the pathogenesis of pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence suggesting a role for both the receptors in the origins of pre-eclampsia and FGR (Plummer et al 2004, Tower et al 2006, Xia et al 2007, comprehensive localisation studies of the AGTR1 and AGTR2 receptors in human placental EVT populations during early pregnancy have not been conducted. Interactions between AGTR1 and AGTR2 have been previously described, through the formation of heterodimers (AbdAlla et al 2001) and the interaction between the two receptors in other tissues is antagonistic in terms of both opposing function and cellular signalling (Dinh et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular apoptosis is regulated by certain proteins, which are apoptosis activating proteins, e.g. Bid, Bak, Bad, and angiotensin II type 1 receptor (AGTR1) [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent haplotype analysis of the AT 2 receptor gene has revealed that four common haplotypes account for over 90% of the haplotypes present in a Caucasian population. 8 Furthermore, the -1332G/A and 3123C/A polymorphisms are in high linkage disequilibrium.…”
Section: Introductionmentioning
confidence: 99%